Development of a Theoanthropoecocentric-Based Islamic Education Curriculum - Ritonga, Robiahasna; Lubis, Safnan; Thoat, Salman (Studi Multidisipliner: Jurnal Kajian Keislaman, 2025)
This research aims to develop the concept of an Islamic Education curriculum that is oriented to the theoanthropocentric paradigm, which is an approach that combines the dimensions of divinity (theocentric), humanitarian (anthropocentric), and ecological (ecocentric) in an integrated manner. This research uses a descriptive qualitative method with a literature study approach and content analysis of Islamic educational literature, curriculum theory, and theoanthropocentric concepts. The data is analyzed interpretively to formulate the principles, structure, and direction of holistic curriculum development. The results of the study show that the theoanthropocentric Islamic Education curriculum requires the integration of worship values, humanitarian ethics, and ecological awareness in every component of the curriculum, including objectives, materials, learning methods, and evaluation. This curriculum places humans as caliphs who are responsible not only to God and others, but also to the preservation of nature. The resulting curriculum model emphasizes contextual learning, hands-on experience, and character building based on ecological spirituality. This study concludes that the theoanthropocentric paradigm offers a relevant conceptual framework to answer the challenges of contemporary Islamic education. The curriculum built through this approach has the potential to create students who are religious, humanist, and ecological, and in line with the goals of Islamic education that are oriented towards sustainability and universal benefit.